Incidence of medication-related osteonecrosis of the jaw and associated antiresorptive drugs in adult Finnish population - Miika Kujanpää; Ville Vuollo; Antti Tiisanoja; Marja-Liisa Laitala; György K. Sándor; Saujanya Karki (Scientific Reports)
Abstract This retrospective study aimed to evaluate the incidence of medication-related osteonecrosis of the jaw (MRONJ) and associated antiresorptive drugs in the Finnish population. All adult patients (aged 18 years and older) who were prescribed with antiresorptive drugs (AR) during 2013–2015 were included in this study. A total of n = 58,367 patients met the inclusion criteria and were followed up until 2020. The outcome variable was the diagnosis of MRONJ during the study period. Patients’ age, gender, type of AR prescribed, reason for using AR drugs, use of corticosteroids, use of vascular endothelial growth factor (VEGF) inhibitors were used as covariates. The incidence of MRONJ was 0.3% in low-dose and 9.0% in high-dose AR recipients in this study population. The risk of developing MRONJ among denosumab users was 5 times higher in both low-dose and high-dose AR recipients compared to bisphosphonates users. Simultaneous use of corticosteroids in addition to AR drug increased the risk of developing MRONJ by 2 times in high-dose recipients and 6 times in low-dose recipients. In conclusion, male, denosumab, any type of cancer diagnosis, high dose of AR drug and simultaneous use of corticosteroids were the most noteworthy risk factors for MRONJ.